Prosodic analysis of school-age children with and without autism spectrum disorder (ASD) diagnosis: a comparative study - Sepúlveda Contardo, Miguel; Illanes Riquelme, María José; Jara Lavín, Katherine; Paredes Fuentes, Valentina; Zambrano Viedma, Valentina (Revista de Investigación en Logopedia, 2024)
Autism Spectrum Disorder (ASD) is characterized by deficiencies in communication and social interaction, including prosody. Alterations such as monotony, difficulty in volume control, and inappropriate accents are mentioned, along with a disconnect between intonation and meaning. However, the literature is not precise about these characteristics in early stages. Thus, our objective was to compare prosodic speech differences between schoolchildren diagnosed with ASD and those with neurotypical development. Using an observational, cross-sectional, and comparative design, with non-probabilistic convenience sampling, 37 participants aged 7 to 11 years (17 with ASD diagnosis and 20 neurotypical) were included in the elementary school stage with acquired literacy. Each family conducted the sample collection, requesting the reading of the "Grandfather's Text" and the phrase "This is my house," prolonging the final /a/. F0, intensity, quantity and duration of pauses, speed, and accents were analyzed using Mann-Whitney T and U tests. The results only show a trend in intensity and quantity of pauses between both groups, but without statistically significant differences. The absence of differences could be attributed to the developmental stage of the participants. Considering the limitations (small sample, variability of results in individuals, sample collection), we propose to delve deeper into this matter by making the necessary adjustments to continue contributing to the study of this communicative skill in this population.
Keywords: Autism spectrum disorder; Childhood; Communication; Pragmatic; Prosody